Reaproveitamento de cavacos de titânio gerados na indústria de implantes ortodônticos para a obtenção de diferentes morfologias de carbonetos depositados a arco elétrico - José Gedael Fagundes Júnior (2020)
Titanium carbides (TiC) have been applied in several studies, as one of the main components for hardfacing, due to its wear resistance properties. However, the factors that affect carbide morphology have different models as reported by the literature. In the present study, graphite and chips from titanium alloys, generated in the manufacturing processes of orthodontic implants were applied as components of the flux in experimental tubular wires. The addition of rutile (TiO2), calcite (CaCO3) and fluorite (CaF2) in the flow of the tubular wires showed effects with significant differences regarding the behaviour of electrical signals and metal transfer. On the other hand, the different chemical compositions of the flux did not promote a significant effect on the shape of the TiC, which presented a morphology mostly faceted for all conditions. Flux with addition of TiO2 showed regions with the formation of agglomerated TiC, established by high values of volumetric fractions of the carbides, establishing a non-faceted morphology. This behaviour was attributed to the offer of titanium and carbon in these regions, indicating that higher levels of these elements may affect the morphology of TiC. In this way, a new experimental design was performed based on the variation of the amount of flux, deposited directly on the base metal, confirming the effects of the amount of flux on the TiC morphology. By the position for each chemical composition on the Fe-Ti-C ternary diagram, it was possible to establish a new model to predict the morphology of the titanium carbides.